Angel and the badman - Grant, James Edward, 1905-1966; Wayne, John, 1907-1979; Russell, Gail, 1924-1961; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Production, 1947)
Quirt Evans is a notorious gunfighter who's wounded and sheltered by a Quaker family. Attracted to the family's angelic daughter, the hard-bitten Evans undergoes a slow and subtle character transformation, but is still obsessed with killing Laredo Stevens, the man who murdered his foster father. Wistful McClintok is the single-minded sheriff who's determined to bring Evans and Stevens to justice.
John Wayne, Gail Russell, Harry Carey, Bruce Cabot, Irene Rich, Lee Dixon.
Photography, Archie J. Stout; music, Richard Hageman; editor, Harry Keller; film producer, John Wayne.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Outlaws -- West (U.S.) -- Drama; Quakers -- Drama; Sheriffs -- Drama; Western films; Feature films; Fiction films; Internet videos; Streaming video